Performance of the UroVysion® FISH assay for the diagnosis of malignant effusions using two cutoff strategies - Débora C. B. Rosolen; Daniel K. Faria; Caroline S. Faria; Leila Antonangelo (Cancer Medicine, 2018)
Abstract The cytological examination of cavity fluids has limited sensitivity in the diagnosis of malignancy. Aneuploidy, which is commonly observed in neoplastic cells, could potentially be used as an ancillary diagnostic tool. To evaluate the detection of aneuploid cells in cavitary effusion samples using the fluorescence in situ hybridization (FISH) assay UroVysion® with some adaptations and two different cutoff strategies. Seventy samples of pleural or peritoneal fluid with positive (n = 40), negative (n = 15), or suspicious (n = 15) oncotic cytology were subjected to FISH assay with the multitarget UroVysion® kit, which is composed of probes that hybridize to the centromeric region of chromosomes 3, 7, and 17 and to the locus 9p21. FISH performance was evaluated using two different cutoffs: (1) the manufacturer's cutoff (M‐FISH) and 2) a proposed cutoff (P‐FISH). Using M‐FISH, the diagnostic sensitivity was 57.1%, specificity 87.5%, and accuracy 60.0%; with P‐FISH, the sensitivity was 87.3%, specificity 71.4%, and accuracy 85.7%. When combined with cytology, the sensitivity, specificity, and accuracy were 88.0%, 83.3%, and 87.8%, respectively. Malignant cells presented a predominance of chromosomal gains. The UroVysion® test using the P‐FISH cutoff was effective in demonstrating aneuploid cells in all malignant effusions, confirming the diagnosis of malignancy even in cases with suspicious cytology.